2011
DOI: 10.1097/gim.0b013e3182142966
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular abnormalities in late-onset Pompe disease and response to enzyme replacement therapy

Abstract: Purpose We evaluated the prevalence of cardiovascular abnormalities and the efficacy and safety of enzyme replacement therapy (ERT) in patients with late onset Pompe disease. Methods Ninety patients were randomized 2:1 to ERT or placebo in a double-blind protocol. Electrocardiograms (ECG) and echocardiograms were obtained at baseline and scheduled intervals over the 78-week study period. Baseline cardiovascular abnormalities, and efficacy and safety of ERT were described. Three pediatric patients were exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 42 publications
2
41
0
9
Order By: Relevance
“…We agree with Forsha et al 1 that further studies are needed to evaluate cardiac effects of ERT in late-onset Pompe disease and would like to emphasize that they should include childhoodand juvenile-onset cases.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…We agree with Forsha et al 1 that further studies are needed to evaluate cardiac effects of ERT in late-onset Pompe disease and would like to emphasize that they should include childhoodand juvenile-onset cases.…”
supporting
confidence: 59%
“…Forsha et al 's study 1 is one of the first to report on the cardiac response to ERT in patients with late-onset Pompe disease. Although they found that cardiovascular parameters were not affected by ERT, it is unclear in the paper whether the PR interval of two patients improved after 78 weeks of ERT or if they simply dropped out of the study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In untreated late onset patients, muscle strength and pulmonary function usually deteriorate, leading in a large majority of patients to wheelchair and need of respiratory support [4,5]. Cardiac involvement, characterized by decreased left ventricular systolic function or elevated left ventricular or septum mass on echocardiogram, has been recently reported in few adult patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a relatively large cohort of adults (87 patients, median age 44 years old, 51% males) with Pompe disease has been described. 40 A short PR interval was present in 10% of the patients, 7% showed a decreased left ventricular systolic function, and 5% had cardiomyopathy (increased left ventricular mass by echocardiography). Interestingly, no changes in cardiovascular status associated with ERT were observed.…”
Section: The Point Of View Of the Pulmonologistmentioning
confidence: 99%